Behind the post-truth world: A philosophical perspective on information and media literacy - Martínez-Ávila, Daniel; Mello, Mariana Rodrigues Gomes de[UNESP]; Borges, Ellen Valotta Dias [UNESP]; Ottonicar, Selma Leticia Capinzaiki [UNESP] (IGI Global, 2020)
The purpose of this chapter is to discuss information and media literacy from a philosophical perspective. This kind of discussion is important because it brings together scientific knowledge and philosophy. The authors base their arguments on some discussions about the Theory of Knowledge, such as the problem of truth, as well as philosophers such as Nietzsche and Foucault. This chapter is interdisciplinary, and it results in the evolution of information and media literacy theory. This chapter also aims to consider the power games that encourage fake news. These games are influenced by ideological aspects of the post-truth world.